2020
DOI: 10.3390/en13123038
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Sub and Supercritical Cryogenic Fluid Dynamics in Conditions Relevant to Novel Ultra Low Emission Engines

Abstract: In this paper we provide insight into the thermophysical properties and the dynamics of cryogenic jets. The motivation of the work is to optimise the use of cryogenic fluids in novel ultra low emission engines. For demonstration, we use conditions relevant to an internal combustion engine currently being developed by Dolphin N2 and the University of Brighton, the CryoPower recuperated split cycle engine (RSCE). The principle of this engine is a split-cycle combustion concept which can use cryogenic injection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Therefore, the contribution of sgs transport properties (like turbulent viscosity) on top of accurate, but small, molecular real-fluid transport properties appears questionable. Interestingly, in the study of Gopal et al [40], a two-fluid model with implicit LES assumption was successfully applied, using an interface compression method to deal with supercritical states, by making the interface term vanish above the critical pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the contribution of sgs transport properties (like turbulent viscosity) on top of accurate, but small, molecular real-fluid transport properties appears questionable. Interestingly, in the study of Gopal et al [40], a two-fluid model with implicit LES assumption was successfully applied, using an interface compression method to deal with supercritical states, by making the interface term vanish above the critical pressure.…”
Section: Introductionmentioning
confidence: 99%
“…A schematic diagram of the concept RSCE accompanied with an entropy diagram is shown below in Figure 1. The second variant, Cryopower further increases the efficiency potential towards 60% by utilising liquid nitrogen (LN 2 ) as the compression stage coolant [5,25]. This has a twofold effect on both efficiency and emissions.…”
Section: Basic Principlesmentioning
confidence: 99%
“…LN 2 can be easily produced from excess renewable energy, providing a clean energy vector and store which utilises primarily cheap and easily recyclable elements. Isothermal compression using LN 2 will not be discussed further in this paper but is the subject of ongoing research [25,26]. Preliminary emissions results from the research combustion engine using air diluted with nitrogen are reported in past research [8], as well as detailed analysis of the RSCE thermodynamic cycle with isothermal compression [8,17,18], and will not be discussed or investigated in this piece of work.…”
Section: Basic Principlesmentioning
confidence: 99%
“…A computational grid size of 150 mm was selected. Fluid properties were derived from the Peng-Robinson equation of state that comes with the Aspen software and is known to be accurate at cryogenic conditions [32]. A temperature-dependent heat capacity model based on a linear fit through the earlier reported experimental data was implemented.…”
Section: Modellingmentioning
confidence: 99%